Ordenamento territorial e sustentabilidade socioambiental: estratégias integradas para o desenvolvimento do Município de Covalima – Timor-Leste - Cruz, Rui António da (2018)
Timor-Leste, including Covalima, needs to study environmental issues and Territorial Planning (OT) to enable a less conflictive relationship between society and nature. The OT that use Zoning as technical and legal instruments are particularly relevant, seeking to reconcile the spatial regionalization associated the society needs, considering the support capacity of the Covalima territory. Covalima is building under the Nacional Development Plan (PDN). Emerges the need for intervention on the territory, the adoption of attitudes less confrontational that makes possible the harmony between Society and Nature. The objective of this research is the Ecological-Economic Zoning (ZEE) that allows methodological strategies that can subsidize environmental management practices under the OT prospects socially balanced and ecologically viable. It is a proposal of a strategic methodological model to Covalima's OT using environmental management establishing as premise of development that rationalizes the compartmentalization of land use and occupation, minimizing conflicts such as: lack of compartmentalisation of soils according to their specific characteristics; injustice in the distribution or balanced occupation of human settlements and social, cultural and economic activities; land colonization disorderly manner and destruction of fragile ecosystems in the context of a balanced urban settlement; inefficiency of management of natural resources and inadequate use of these resources, and the devaluation and extinction of traditional practices in environmental preservation are among the main social factors for the degradation of local well-being, whether in ecosystems or in different anthropic occupations. The Territorial Environmental Management and its representative approaches to the different theoretical-methodological currents come to dialogue about the importance of OT, with the main tool the ZEE, an instrument regulating anthropic interventions in environmental units. The achievement of objectives and analyzes were based on systemic studies incorporating socio-environmental aspects of the sites. For the ZEE, the digital analysis techniques that support the characterization and geo-environmental compartmentalization of Covalima including the interpretation and elaboration of thematic maps using the Satellite digital analysis techniques were applied, TM-LANDSAT 7 + ETM 2000 and geoprocessing, with prior knowledge as well as bibliographical, geocartographic and photointerpretation documents based on the knowledge of environmental systems, and the use and territorial occupation of Covalima. In the field, interviews were conducted with the population and the competent leader of the municipality. This research led to the partitioning of environmental systems and subsystems, as well as the socioeconomic aspects, establishing the classification of areas of interest singularly adopting the definition and function of the same. According to the synthesis and geo-environmental systems and the use and occupation maps, obtained the results, it was possible to enable five Environmental Protection sub-areas, three Environmental Recovery sub-areas, three sustainable use sub-zones, a Landscape and Cultural Protection sub-zone, an Urban Expansion sub-area, and two sub-zones of Ethnic Superposition. Thus, these sub-areas the Government may intervene as future scenarios proposed in the integrated management plan, and future scenarios in the prospective sustainability of these environmental units in the Municipality of Covalima.